Effect of light therapy on performance and daytime sleepiness in youth shooting athletes - Tay, Vanes Ling Li (2019)
Background: Sleep restriction has adverse effects on exercise performance and increases the risk of injuries. While research has been conducted on methods to alleviate the negative effects of insufficient sleep on athletes, few have looked into the use of bright light therapy (BLT). Purpose: This study aims to determine the effect of BLT on shooting performance, daytime sleepiness and shooting consistency. Method: This study adopted a within-subject, randomised crossover design. Data of 14 elite youth shooters (age: 14.1 ± 0.8 years) who were able to adhere to the schedule, screened and fulfilled the chronically sleep deprived criteria, were used. They underwent 2 light conditions - active and placebo light for 30 minutes on two separate test session, spaced one week apart. Epworth Sleepiness Scale for Children and Adolescents was completed before and after the intervention, before they fired 60 shots. A paired t-test was used to compare shooting performance, while two-way repeated measures ANOVA was used to compare daytime sleepiness and series scores between conditions and across time. Results: There were no significant differences in total shot scores, daytime sleepiness, as well as first and last series scores between both conditions (p < 0.05). A significant negative correlation was observed between total shot scores and daytime sleepiness in pistol shooters (r = -0.54; p < 0.05). Conclusion: Exposure to BLT has no effect on shooting performance, daytime sleepiness and shooting consistency. Future research may consider modifying duration, time of light exposure or test on a group of non-sleep-deprived subjects.